Learning Circles: One form of knowledge production in social action research - Ravensbergen, Frances; Vanderplaat, Madine (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2010)
This paper explores the use of “learning circles” as one form of knowledge production in social action research. It reports on a project that used learning circles as a setting within which to increase the engagement of people living with low income in developing strategies for the reduction and elimination of poverty in Canada. It presents the process and reflections, analysis and recommendations of 55 project participants and the authors.